INFLUENCE OF INTERNAL FACTORS ON STRATEGY IMPLEMENTATION IN MACHAKOS COUNTY GOVERNMENT, KENYA - Mutuku, Linda; Misango, PhD, Dr. Sedina (European Journal of Business and Strategic Management, 2020)
Purpose: Despite the critical role played by County Governments in strategic planning, they are faced by inability to implement the strategies effectively leading to poor performance characterized by several challenges such as: misappropriation of funds, corruption, delay in services and poor service delivery. The purpose of the study was to determine the influence of internal factors on strategy implementation in Machakos County Government. Methodology: This study adopted cross-sectional survey research design. The population of the study was 1962 staff of Machakos County Government drawn from the different departments of Machakos County Government. Stratified sampling was applied to select 196 respondents from the population. Questionnaires having open and closed ended questions relating to the objectives were used to collect primary data. Both descriptive and inferential statistics were applied in the study to analyze data from the questionnaires. SPSS version 24.0 software was used to code and analyze data and findings tabulated and presented in forms of tables. Results: The findings in regards to the influence of leadership skills on strategy implementation showed that the relationship between the leadership in place and subordinates was significant with a beta coefficient of 0.302.The study also found out that: Training employees is key to strategy implementation with a coefficient of 0.429.; Resource allocation played a big role in ensuring strategy implementation with a coefficient of 0.279 The respondents were in agreement that the management should involve them at all times in strategy implementation with a coefficient of 0.040 The study concluded that Strategic implementation in County governments is not guided by any explicit policy guideline from the national government and that most leaders charged with strategy implementation lack skills and knowledge on strategic formulation and hence cannot offer effective leadership to the process. Unique Contribution to Theory, Practice and Policy: The study therefore recommends the following: County governments to draw and disseminate policy guidelines on formulation of strategic plans for it to be embraced as a management tool; Government training institutions to include strategic implementation topic into their curriculum so that all cadres of employees are equipped with needed skills and knowledge.